Investigating the factors that constrain growth of funded SMMEs in KwaZulu Natal Province: a case study of Ithala Development Finance Corporation - Mubonderi, Joseph (Research of GSB, 2018)
This research investigates the factors that affect the performance of funded Small, Medium and Micro Enterprises (SMMEs) in the KwaZulu Natal (KZN) province of South Africa. Many studies have shown that access to financing is the major challenge facing small enterprises in Africa due to a number of factors which include information opacity and lack of collateral. Other researches however noted that many of the SMMEs in South Africa that had received funding from agencies set by the government or other private sources of funding struggled to attain sustainable growth and many of them failed, something which is puzzling to authorities and academics alike. This study sought to investigate possible causes of such failures through investigating a sample of 300 SMMEs that had received agency funding and operating in the KZN province. The study reveals that there are poor management practices within the funded SMMEs, with weak financial management and control systems in place. The study also reveals the lack of use of technology to leverage business growth. In addition the study reveals that there are no additional support structures put in place for funded enterprises which adversely affect their growth prospects. The study also raises important questions about the affordability and the structuring of the terms of financial support facilities made available to the SMMEs. Finally the study proffers policy recommendations to support the growth of SMMEs and ultimately to see them grow into large corporations.